A Highly Sensitive and Specific Probe-Based Real-Time PCR for the Detection of Avibacterium paragallinarum in Clinical Samples From Poultry - Kuchipudi, Suresh V.; Yon, Michele; Surendran Nair, Meera; Byukusenge, Maurice; Barry, Rhiannon M.; Nissly, Ruth H.; Williams, Jen; Pierre, Traci; Mathews, Tammy; Walner-Pendleton, Eva; Dunn, Patricia; Barnhart, Denise; et al. (Frontiers in Veterinary Science, 2021)
Avibacterium paragallinarum (historically called Hemophilus paragallinarum) causes infectious coryza (IC), which is an acute respiratory disease of chickens. Recently, outbreaks of IC have been reported in Pennsylvania (PA) in broilers, layer pullets, and laying hens, causing significant respiratory disease and production losses. A tentative diagnosis of IC can be made based on history, clinical signs, and characteristic gross lesions. However, isolation and identification of the organism are required for a definitive diagnosis. Major challenges with the bacteriological diagnosis of A. paragallinarum include that the organism is difficult to isolate, slow-growing, and can only be successfully isolated during the acute stage of infection and secondary bacterial infections are also common. As there were very limited whole genomes of A. paragallinarum in the public databases, we carried out whole-genome sequencing (WGS) of PA isolates and based on the WGS data analysis; we designed a novel probe-based PCR assay targeting a highly conserved sequence in the recN, the DNA repair protein gene of A. paragallinarum. The assay includes an internal control, with a limit of detection (LOD) of 3.93 genomic copies. The PCR efficiency ranged between 90 and 97%, and diagnostic sensitivity of 98.5% compared with conventional gel-based PCR. The test was highly specific, and no cross-reactivity was observed with other species of Avibacterium and a range of other common poultry respiratory viral and bacterial pathogens. Real-time PCR testing on 419 clinical samples from suspected flocks yielded 94 positives and 365 negatives in agreement with diagnostic bacterial culture-based detection. We also compared the recN PCR assay with a previous HPG-2 based real-time PCR assay which showed a PCR efficiency of 79%.